Occurrence of phthalate metabolites in human urine from several Asian countries - Guo, Y.; Alomirah, H.; Cho, H.S.; Minh, T.B.; Mohd, M.A.; Nakata, H.; Kannan, K. (2011)
The occurrence of 14 phthalate metabolites was found in human urine samples collected from seven Asian countries: China, India, Japan, Korea, Kuwait, Malaysia, and Vietnam. Phthalate metabolites were found in all samples, indicating widespread exposure of humans to phthalates in these Asian countries. The highest total (the sum of 14 phthalates) phthalate metabolite concentrations were found mL), China (234 ng/mL), Vietnam (133 ng/mL), Japan (120 in samples collected from Kuwait (median: 1050 ng/mL), followed in decreasing order by samples from India (389 ng/mL), China (234 ng/mL), Vietnam (133 ng/mL), Japan (120 ng/mL), Korea (117 ng/mL), and Malaysia (94.9 ng/mL). The creatinine, respectively. Monomethyl phthalate (mMP), Korea, and Malaysia were 692, 506, 289, 119, 103, 104, and 169 creatinine-adjusted median concentrations of total phthalates ng/mL), Korea (117 ng/mL), and Malaysia (94.9 ng/mL). The for urine samples from Kuwait, India, China, Vietnam, Japan, monoethyl phthalate (mEP), mono (2-isobutyl phthalate) (miBP), mono-n-butyl phthalate (mEP), and metabolites of di-(2-ethylhexyl) phthalate (DEHP) were the dominant compounds, collectively accounting for > 95 of the total concentrations in the samples from the seven countries. The profiles of urinary phthalate metabolite concentrations varied among the samples collected from the seven countries. Urine samples from Kuwait contained the highest concentrations of mEP (median: 391 ng/mL), mBP (94.1 ng/mL), and the metabolites of DEHP (202 ng/mL), whereas samples from China and Japan contained the highest concentrations of miBP (50.8 ng/mL) and niMP (17.5 ng/mL), respectively. mEP was the predominant metabolite in urine samples from India and Kuwait (accounting for 49 of the total), mBP and miBP were the predominant compounds in samples from China (52), and DEHP metabolites were the predominant compounds in samples from Korea (46) and Vietnam (52). Based on the urinary concentrations of mEP, mBP, miBP, and DEHP metabolites of the samples from the seven Asian countries, we estimated daily intake rates of diethyl phthalate (DEP), dibutyl phthalate (DBP), and DEHP. The results indicated that people in the seven Asian countries are exposed to DEP, DBP, and DEHP at levels well below the reference doses (RfD) suggested as unsafe by the U.S. Environmental Protection Agency (EPA). The estimated exposure doses to DEHP in Kuwait, however, were above the RID recommended by the EPA.